Code-switching, Structural change and Convergence: A study of Sesotho in contact with English in Lesotho - Semethe, Mpho Maboitumelo (Linguistics, 2020)
This study investigates whether code-switching practices among Sesotho-English bilinguals promote convergence between Sesotho and English. First, the study identifies different types and patterns of code-switching between Sesotho and English and analyses them using Myers-Scotton’s (1993) Matrix Language Frame model and Myers-Scotton and Jake’s (2000) 4-M model. Second, it applies the ML turnover in order to detect convergence in Sesotho-English code-switching data and to observe which direction it takes. The study also explores other factors contributing to change in the structure of Sesotho, which are not necessarily influenced by convergence. In conducting this study, data was collected through interviews that were held with younger bilingual speakers from different tertiary institutions in and around Maseru (Lesotho) and through recorded youth-centred phone-in radio programmes. Findings from the analysis of data reveal simple to complex Sesotho-English code-switching performance of various types and strategies. Findings also show through the existence of composite language in Sesotho-English code-switching that there is a turnover in the ML, which indicates a development of an asymmetrical convergence between Sesotho and English. It was also discovered that, although other changes in the Sesotho structure are not English influenced, they are enhanced mostly by younger urban bilingual speakers’ frequent “looser” approach to Sesotho. This is an indication that Sesotho’s susceptibility to change correlates strongly with age; that is, both the length of time contact between Sesotho and English has existed, and the generation in which change is mostly found. This thesis adds and documents a different perspective to the previously recorded changes on Sesotho-English contact in Lesotho.